(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses aspects of improving the effectiveness of training in higher education, strengthening future teachers’ sustainable interest in science, educating mature specialists from them by achieving a broad and deep understanding of the foundations of science.